Reasoning reasonably in mathematics - Boavida, Ana Maria; Oliveira, Hélia; Mason, John (Associação de Professores de Matemática, 2012)
Two tasks designed to encourage mathematical reasoning without any need for calculations were presented to students with the aim of seeking evidence of different forms of attention (Mason, 2003), and using these to learn about the tasks and about students’ power to reason ‘reasonably’ in mathematics. The first task that involves locating a secret place using an applet was solved by two pairs of grade 4 Portuguese students. The second task, involving the structure of magic squares, was proposed to two classes of Portuguese students, aged 12-13. The interactions between pairs of students and teacher probes were taped and transcribed, and, in the second one, students’ written responses were collected as well. In both cases, the data were analysed using the fivefold framework of microstructure of attention. The first case gives evidence that young students can reason ‘reasonably’ but that there are delicate shifts which may require sensitivity on the part of the teacher to help students progress. In the second case, the data analysis shows that these students displayed the power to reason ‘reasonably’ in mathematics, and that difficulties can be accounted for in terms of not only what was being attended to, but the form of that attention.

Foram propostas duas tarefas a alunos portugueses do ensino básico para os encorajar a raciocinar matematicamente sem o recurso a cálculos, com o objetivo de procurar evidências sobre diferentes formas de atenção (Mason, 2003) e de usar essas evidências para refletir sobre as tarefas e sobre a capacidade dos alunos raciocinarem “com razoabilidade” em matemática. A primeira tarefa, centrada na localização de um lugar secreto usando uma applet, foi resolvida por dois pares de alunos do 4.º ano de escolaridade. A segunda, envolvendo a estrutura de quadrados mágicos, foi proposta a duas turmas do 7.º ano de escolaridade. Em qualquer dos casos, procedeu-se à gravação e transcrição das interações entre alunos e professor e na segunda tarefa recolheram-se, ainda, as resoluções escritas dos alunos. Os dados obtidos foram analisados usando um modelo composto por cinco formas ou microestruturas de atenção. No caso da primeira tarefa, evidencia-se que as crianças são capazes de raciocinar “com razoabilidade” mas que o seu progresso depende de mudanças subtis que requerem sensibilidade por parte do professor. A análise de dados relativos à segunda tarefa, revela, igualmente, que os alunos mostram poder para raciocinar “com razoabilidade”. Revela, ainda, que as suas dificuldades podem ser explicadas não só em termos daquilo que é o objeto da atenção mas também da forma desta atenção.
Keywords: Mathematical reasoning; Structures of attention; Mathematical tasks; Basic education; Raciocinio matemático; Estruturas da atenção; Tarefas matemáticas; Ensino básico